PERAN INSPEKTORAT DALAM MELAKUKAN REVIU PADA LAPORAN KEUANGAN PEMERINTAH DAERAH DI KABUPATEN NABIRE - Monika Helena Maniawasi; Amir Jaya; Amson Padolo (Paulus Journal of Accounting (PJA), 2024)
This study analyzes the role of the Inspectorate in reviewing the Regional Government Financial Report (LKPD) in Nabire Regency. Through qualitative methods, data were collected from interviews, observations, and documentation with seven informants. The results of the study indicate that the role of the Inspectorate is very important in ensuring accountability and transparency of regional finances through systematic review stages, including preparation, data collection, analysis, and follow-up monitoring. The main challenges include limited human resources, budget, and resistance from related agencies. To overcome this, capacity building, technology utilization, and collaboration between parties are needed. With an effective review process, regional financial management can be improved, providing greater benefits to the community, and increasing public trust in the regional government. This study provides strategic insights for better regional financial management.